Efficacy of whole cell vaccine Aeromonas hydrophila on catfish broodstock and it’s offspring resistance againt motile aeromonad septicemia (MAS) - , Sukenda; Kiki Amalia Pratiwi; , Rahman; Dendi Hidayatullah (Jurnal Akuakultur Indonesia)
ABSTRACT